2008
DOI: 10.1590/s0101-20612008000100023
|View full text |Cite
|
Sign up to set email alerts
|

Estabilidade oxidativa e microbiológica em carne de galinha mecanicamente separada e adicionada de antioxidantes durante período de armazenamento a -18 °C

Abstract: No ano de 2005 foram produzidos no Brasil 9,3 milhões de toneladas de carne de frango (AVISITE, 2006). A preferência dos consumidores por cortes de frango ao invés de frangos inteiros, e posteriormente a demanda por filés e produtos de conveniência, trouxe a necessidade de se encontrar meios para aproveitar as enormes quantidades de dorsos, pescoços e ossos, resultantes dos processos de desossa. Estas partes representam cerca de 24% da porção comestível. Com isso, as carnes mecanicamente separadas (CMS) de ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
11

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 13 publications
0
6
0
11
Order By: Relevance
“…Several authors suggest that the reduction of TBARS values observed as a function of storage period is probably associated to the enhancement of polar product concentrations, resulting from the polymerization of secondary products of oxidation (Gatellier et al 2007). The rancidity odor can be detected by trained and nontrained tasters in the range from 0.5 to 1.0 and 0.6 to 2.0 mg MDA/kg (Trindade et al 2008), respectively. Here, the TBARS values were lower than those cited by the previously cited authors and consequently the odor and flavor of rancidity was not detected in the sensory evaluation of formulations.…”
Section: Resultsmentioning
confidence: 99%
“…Several authors suggest that the reduction of TBARS values observed as a function of storage period is probably associated to the enhancement of polar product concentrations, resulting from the polymerization of secondary products of oxidation (Gatellier et al 2007). The rancidity odor can be detected by trained and nontrained tasters in the range from 0.5 to 1.0 and 0.6 to 2.0 mg MDA/kg (Trindade et al 2008), respectively. Here, the TBARS values were lower than those cited by the previously cited authors and consequently the odor and flavor of rancidity was not detected in the sensory evaluation of formulations.…”
Section: Resultsmentioning
confidence: 99%
“…Cured salts are essential ingredients for meat processing and nitrite plays a strong antioxidant role as originally reported by Pearson et al (1977). Nitrite also acts as lipids antioxidant in the mechanical deboning of chicken meat (Trindade et al 2008) and also in CH and JB (Youssef et al 2003;2011). Thus, the objective of this work was to determine quantitatively the amount of lipids and proteins oxidations through the TBARS and carbonyl determinations, respectively.…”
Section: Introductionmentioning
confidence: 86%
“…O eritorbato de sódio, um isômero do ácido ascórbico, apresenta forte efeito antioxidante e é usado na prevenção do desenvolvimento de rancidez oxidativa, quando aplicado em concentrações acima de 100 mg L -1 (Trindade et al, 2008). A crioproteção ocorre quando compostos de baixo peso molecular favorecem termodinamicamente a manutenção das proteínas em sua conformação nativa (Etemadian et al, 2011).…”
Section: Introductionunclassified